The global burden of osteoarthritis hand: lessons from the Global Burden of Disease Study 1990–2021 - Wei, Jiyong; Su, Zhongyi; Pan, Songmu; Zou, Zhuan; Liao, Gui; Li, Guangxiong; Liu, Huijiang; Lan, Guipeng; Gu, Ronghe; Lan, Yanni (Frontiers in Medicine, 2025)
BackgroundHand osteoarthritis (HOA), a disabling musculoskeletal disorder, poses a significant global burden but remains understudied relative to other osteoarthritis (OA) subtypes. Using data from the Global Burden of Disease (GBD) Study 1990–2021, this analysis characterizes HOA epidemiology, temporal trends, and future projections.MethodsGBD 2021 data on HOA incidence, prevalence, and disability-adjusted life-years (DALYs) were stratified by sex, age, Socio-demographic Index (SDI) regions, GBD regions, and countries. Temporal trends (1990–2021) were assessed via estimated annual percentage changes (EAPCs), with future projections (2022–2046) generated using an age-period-cohort (APC) model.ResultsIn 2021, HOA accounted for 10.37 million incidence cases, 194.28 million prevalence cases, and 6.17 million DALYs. Female burdens were 1.8–2.0 times higher than males in absolute terms and 1.75–1.78 times higher in age-standardized rates (ASRs). Incidence cases peaked in advanced ages before declining, while prevalence/DALYs rose monotonically with age. Middle SDI regions had the highest absolute burdens, whereas high SDI regions showed the highest ASRs. Central Asia emerged as a burden hotspot, while minimal health system regions and sub-Saharan Africa had the lowest rates. From 1990 to 2021, global incidences increased 142%. Low/middle-income regions (such as South Asia) saw significant increases, contrasting with declines in high-income areas (such as Western Europe). APC projections indicate continued growth through 2046, with male/female incidences rising 69.6%/51.6% and ASRs increasing for both sexes.ConclusionHOA represents a growing global challenge with pronounced sex/age/regional disparities. Targeted interventions in high-burden regions, aging populations, and risk factor management are critical to mitigate projected burden increases.